Peran Badan Amil Zakat Nasional Kota Banjarmasin dalam Peningkatan Perekonomian Masyarakat - Taufik Hidayat (Management of Zakat and Waqf Journal (MAZAWA), 2020)
The potency of tithe (locally called as zakat) recently is not optimally developed an professionaly managed. Ineffectiveness of operational of tithe collecting agency related to the aspects of administration, distributing, monitoring or in evaluating the tithe has become the factor of this condition. In other word, it can be assumed that the organizational system and management of tithe is still classical, consumptive and lacking of significant social impact. Bassed on that assumption, the role of government is demmed essential in coping with the issue. Through the tithe collecting agency either in local or in national level, it is espected the management of tithe collection can be optimally down. Meanwhile, Baznas in Banjarmasin City is the object of this reseach in which, according to the writer, this institution has played its rule quite well in the attempt of realizing the laws about the management of tithe (zakat) both in collecting, distributing, and using the tithe and in the attempt of developing the people economic through the prorams of Revolving Loan Fund given by Baznas of Banjarmasin City that can influence the development of the Mustahiq economic trough it recently is not fulfilled maximally.